(untitled) (Strathmore Law Journal, 2022)
The current issue that affects Sub-Saharan Africa is the proliferation of unlicensed digital credit providers. These digital credit providers employ the use of information and communication technology in making their loan products attractive. Their loan recovery methods are crude and life-threatening coupled with a very high-interest rate. This article discusses the current situation in Nigeria and Kenya. The Nigerian government, through joint action, carried out a raid on these digital credit providers, freezing their bank accounts and ordering that google play store and apple store should remove them from their platforms. Kenya has been able to put these digital credit providers under the regulation of the Central Bank of Kenya. In its press release dated March 21, 2022, the Central Bank of Kenya (CBK) announced the publication by Legal Notice No. 46 of March 18, 2022, of the Central Bank of Kenya (Digital Credit Providers) Regulations, 2022. The Regulations were issued in accordance with Sections 57(1), 57(3), and 57(4) of the Central Bank of Kenya Act (the CBK Act). They provide for the licensing and oversight of previously unregulated Digital Credit Providers (DCPs). The Regulations are now operational This article examines the regulations and concludes by recommending that Nigeria should emulate Kenya by publishing Central Bank of Nigeria Digital Credit Providers Regulations.